Analytical validation (accuracy, reproducibility, limit of detection) and gene expression analysis of FoundationOneRNA assay for fusion detection in 189 clinical tumor specimens - Daokun Sun; Richard S. P. Huang; Michelle Green; Chenming Cui; Saumya D. Sisoudiya; Andrej Savol; Chang Xu; Cui Guo; Joel Skoletsky; Justin M. Allen; Khaled Tolba; Varun Pattani; et al. (PLoS ONE, 2025)
Targeted DNA-based comprehensive genomic profiling (CGP) to detect clinically significant alterations is increasingly becoming standard for patients with advanced or recurrent cancer. RNA-based sequencing, however, may improve performance of fusion detection. We developed a robust targeted RNA sequencing assay (FoundationOne®RNA) and evaluated its analytic performance. FoundationOne®RNA is a hybrid-capture based targeted RNA sequencing test designed to optimally detect fusions (318 genes) and measure gene expression (1521 genes). Analytical validation studies were performed in College of American Pathologists (CAP)-accredited and Clinical Laboratory Improvement Amendments (CLIA)-certified lab to assess fusion call accuracy, assay reproducibility, limit of detection (LoD) and gene expression in 189 clinical solid tumor specimens. In the accuracy study, 160 out of 189 biopsy samples which were previously profiled using large-panel DNA- or RNA-based next-generation sequencing (NGS) passed quality control metrics and were studied using the FoundationOne®RNA assay. Analysis of all diagnostic fusions showed a positive percent agreement (PPA) of 98.28%, as well as a negative percent agreement (NPA) of 99.89% when compared to orthogonal assays. The FoundationOne®RNA assay was able to identify a low level BRAF fusion missed by orthogonal whole transcriptome RNA sequencing and was confirmed by fluorescence in situ hybridization (FISH). The range for the minimum RNA input and LoD was determined based on dilutions from 5 fusion-positive cell lines. It spans from 1.5ng (0.5% input) to 30ng (10% input) for RNA input and from 21 to 85 supporting reads for LoD. In the precision study, 10 out of 10 pre-defined target fusions had 100% reproducibility. In our gene expression analysis, multiple gene expression signatures were detected in fusion positive samples. FoundationOne®RNA assay successfully detected oncogenic fusions with high concordance to orthogonal NGS based tests, high reproducibility, and low limit of detection. This study demonstrated the robustness of FoundationOne®RNA and supports its use as a supplement to tissue DNA comprehensive genomic profiling (CGP) in routine clinical practice. Additional work is required to clarify optimal clinical scenarios for fusion detection and enable gene expression biomarkers for clinical use.